Executive function in schizoaffective disorder: A comparative study with schizophrenia, bipolar affective disorder and normal controls. - Sen, Devosri; Sinha, Vinod K.; Jayaswal, Meera; Biswas, Partha S. (Indian Journal of Psychiatry, 2026)
Background: Schizoaffective disorder (SAD), in current literature, lies clinically and prognostically between schizophrenia (SCZ) and bipolar affective disorder (BPAD), with some overlapping neuropsychological deficits in them. Aim: The aim of this study was to investigate whether there was any difference in executive functions among patients of schizoaffective disorder (SAD), schizophrenia (SCZ), bipolar affective disorder with psychotic symptoms (BPAD) and normal controls (NC). Methods: Data were collected by a non-probability purposive sampling technique from a total of 114 psychotic in-patients using inclusion and exclusion criteria. Using standard laboratory procedure, executive functions (Trail Making Test, TMT; Stroop Color-Word Test, SCWT; Spatial Working Memory, SWM; Stockings of Cambridge, SOC; Intra-Extra Dimensional Set Shift, IEDS) of 23 consecutive consenting clinically stable patients of SAD (manic type) were compared with 23 matched (age, gender and handedness) consenting clinically stable patients of each SCZ, psychotic BPAD and NC subjects. Results: Significantly more executive function deficits due to low CW score (F = 35.11,95% CI = 32.12 to 37.09, P <.001), more Stroop interference (F = 6.53,95% CI = 5.12 to 7.11, P <.001) in SCWT and more SWM errors (F = 19.08,95% CI = 17.42 to 21.34, P <.001) were noted in SAD patients than BPAD patients. NC and bipolar group had gradually reduced their percentage of bets in CGT, as they passed through higher probability to lower probability ratios. But both SAD and SCZ patients could not follow this concept, and thus they showed more impulsivity or risk-taking behavior. Conclusion: The CW score, and Stroop interference and number of errors of SWM can differentiate SAD patients from BPAD. The percentage of bets placed in different probability ratios in CGT can differentiate SAD and SCZ patients from BPAD patients neuropsychologically.